Student safety insurance policies in India: a systematic review - Reddy, Muthyala Sudhakara; Venkayalapati, Venkateswarlu (International Journal Of Community Medicine And Public Health, 2020)
Personal accident insurance policy provides complete financial protection to the insured members against uncertainties such as accidental (unintentional) death or bodily injuries. Additionally, it covers permanent (partial/complete) and temporary disabilities resulting from an unintentional injury (UII), but not intentional injury. As such policy confined to the students, it was nomenclated as ‘student safety insurance policy’ (SSIP). Aim of the study was to review the features of various SSIPs in India followed by suggesting to the governments to implement across India. A thorough internet search was carried out using search engines to collect primary data in the public domain regarding SSIPs. Additional information was also collected from the organizations under Right to Information Act 2005 during July to December 2017. The reviewers identified that millions of children died each year from the injuries or violence and millions of others suffer the consequences of non-fatal injuries across the world. Dr. Gururaj estimated that the injuries resulted in the deaths of nearly 100,000 children every year in India among two million children hospitalized. So, certain state governments, districts and universities have taken up ‘SSIPs’ with different features to meet the hospital expenses incurred due to an UII. Unfortunately, if the insured child died/disabled due to an UII, the insurance amount will fulfil future financial needs of the family/disabled. Certain institutions are providing insurance coverage for one of the parents (breadwinner) and exempting future course fee payment also. The reviewers suggested to the government to provide a better student safety insurance policy across India with the amalgamation of the key features of all safety insurance policies.